Linking howler monkey ranging and defecation patterns to primary and secondary seed dispersal - Fuzessy, Lisieux [UNESP]; Sobral, Gisela; Culot, Laurence [UNESP] (Wiley, 2022)
To define the chances of a dispersed seed to produce a new recruit, it is essential to consider all stages of the dispersal process. Howler monkeys are recognized to have positive impacts on forest regeneration, acting as primary dispersers. Furthermore, dung beetles attracted to their feces protect the seeds against predators, and provide a better microenvironment for germination due to the removal of fecal matter, to seed burial, and/or by reducing the spatial aggregation of seeds in fecal clumps. Despite the recognized positive effects of primary seed dispersal through defecation by howler monkeys for plant recruitment, there are some important aspects of their behavior, such as the habit of defecating in latrines, that remain to be explored. Here, we investigated the fate of Campomanesia xanthocarpa seeds defecated by brown howlers, Alouatta guariba clamitans, and the secondary seed dispersal by dung beetles, considering how this process is affected by the monkey's defecation patterns. We found that brown howler monkeys dispersed seeds from several species away from fruit-feeding trees, partly because defecation under the canopy of such trees was not very frequent. Instead, most defecations were associated with latrines under overnight sleeping trees. Despite a very similar dung beetle community attracted to howler feces in latrines and fruit-feeding sites, seeds were more likely to be buried when deposited in latrines. In addition, C. xanthocarpa seeds showed higher germination and establishment success in latrines, but this positive effect was not due to the presence of fecal matter surrounding seeds. Our results highlight that A. guariba clamitans acts as a legitimate seed disperser of C. xanthocarpa seeds in a preserved context of the Brazilian Atlantic Forest and that defecations in latrines increase the dispersal effectiveness.